Performance of West African Dwarf Sheep (the Djallonke) fed fattening diets containing agro-industrial by-products in Ghana - Baiden, R.Y.; Obese, F.Y. (Ghanaian Journal of Animal Science, 2010)
A study was conducted to evaluate the performance of Djallonke rams on fattening diets containing Panicum maximum and concentrate rations formulated from agro-industrial by-products (AIBPs). Three concentrate diets were formulated to contain approximately 12.6% crude protein. Twenty-four Djallonke rams aged between eight to eighteen months with an average weight of 14.35 0.28kg were divided into three groups of eight animals each on age and weight basis and randomly assigned to three dietary treatments. Each animal was offered 250 grams of the concentrate diet daily. The performance of the animals on the various diets was comparable (P>0.05) for all the parameters measured. The rams grew at a rate of 63.21-71.43g/d. Dry matter intake ranged from 88.92g/day/kgw 0.75. Dry matter digestibility was between 71.04 % - 74.78% Dietary treatment did not significantly (P>0.05) affect the haematological values measured. Packed cell volume ranged from 27.45-29.13%. Haemoglobin was between 12.41 -13.60 g/ 100 ml, red blood cell, 11.42 x103/µl -11.92x103 /µl and white blood cell, 8.94 - 10.21 x 103/µl. All these values were within the normal physiological range reported for sheep. It is concluded that AIBPs including cotton seed cake, wheat bran and groundnut skin could be considered in fattening diets for sheep in Ghana.
Keywords: Growth; Health; Agro-Industrial By Products; Feed Intake; Digestibility